Improving the CH1-CK heterodimerization and pharmacokinetics of 4Dm2m, a novel potent CD4-antibody fusion protein against HIV-1. Issue 4 (18th May 2016) - Chen, Weizao; Bardhi, Ariola; Feng, Yang; Wang, Yanping; Qi, Qianqian; Li, Wei; Zhu, Zhongyu; Dyba, Marzena A.; Ying, Tianlei; Jiang, Shibo; Goldstein, Harris; Dimitrov, Dimiter S.
ABSTRACT: We previously described 4Dm2m, an exceptionally potent broadly neutralizing CD4-antibody fusion protein against HIV-1. It was generated by fusing the engineered single human CD4 domain mD1.22 to both the N and C termini of the human IgG1 heavy chain constant region and the engineered single human antibody domain m36.4, which targets the CD4-induced coreceptor binding site of the viral envelope glycoprotein, to the N terminus of the human antibody kappa light chain constant region via the (G4S)3 polypeptide linkers. However, therapeutic use of 4Dm2m was limited by its short in vivo half-life. Here, we show that a combination of three approaches have successfully increased the persistence of 4Dm2m in mice. First, to stabilize the scaffold, we enhanced heterodimerization between the heavy chain constant domain 1 (CH1) and kappa light chain constant domain (CK) by using structure-guided design and phage-display library technologies. Second, to address the possibility that long polypeptide linkers might render fusion proteins more susceptible to proteolysis, we shortened the (G4S)3 linkers or replaced them with the human IgG1 hinge sequence, which is naturally designed for both flexibility and stability. Third, we introduced two amino acid mutations into the crystallizable fragment (Fc) of the scaffold previously shown to increase antibody binding to the neonatal Fc receptor (FcRn) and prolong half-lives in vivo. Collectively, these approaches markedly increased the serum concentrations of 4Dm2m in mice while not affecting other properties of the fusion protein. The new 4Dm2m variants are promising candidates for clinical development to prevent or treat HIV-1 infection. To our knowledge, this is the first report on stabilized CH1-CK, which is potentially useful as a new heterodimerization scaffold for generation of bispecific and multispecific antibodies or proteins with a more favorable pharmacokinetic profile.